2021
DOI: 10.1039/d1ma00130b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of a Ni3N OER precatalyst in Fe-purified alkaline media: the impact of self-oxidation and Fe incorporation

Abstract: The effects of self-oxidation and Fe incorporation in a Ni3N electrocatalyst towards its water oxidation activity were examined in alkaline media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 86 publications
7
53
0
Order By: Relevance
“…In the Ni 2p spectra of Ni 2 Mo 3 N/NF ( Figure 4 b), Ni 0 peaks disappeared, and Ni 2+ and Ni 3+ peaks intensified, possibly due to the formation of NiO x or NiOOH species. The peaks can be deconvoluted into three pairs with binding energies of 855.2/872.5, 856.4/874.2, and 861.3/879.4 eV corresponding to the 2p 3/2 /2p 1/2 doublets of Ni 2+ , Ni 3+ , and satellites [ 27 , 44 , 45 , 51 ]. In Ni-containing catalysts, surface NiO x species are generated in a low potential range below 1.35 V, which are further oxidized to NiOOH at ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Ni 2p spectra of Ni 2 Mo 3 N/NF ( Figure 4 b), Ni 0 peaks disappeared, and Ni 2+ and Ni 3+ peaks intensified, possibly due to the formation of NiO x or NiOOH species. The peaks can be deconvoluted into three pairs with binding energies of 855.2/872.5, 856.4/874.2, and 861.3/879.4 eV corresponding to the 2p 3/2 /2p 1/2 doublets of Ni 2+ , Ni 3+ , and satellites [ 27 , 44 , 45 , 51 ]. In Ni-containing catalysts, surface NiO x species are generated in a low potential range below 1.35 V, which are further oxidized to NiOOH at ca.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate the formation of amorphous surface oxide species from crystalline nitride species. However, in the Ar-sputtered Mo 3d and N 1s spectra of Ni 2 Mo 3 N/NF after the durability test ( Figure S5 ), the nitride-related peaks appeared again [ 44 , 51 ]. In Figure S1a , Mo 0 and Mo 3+ peaks showed up as in the fresh Ni 2 Mo 3 N/NF sample, and the Mo 3d spectra showed four Mo oxidation states: Mo 0 (228.3/231.9 eV), Mo 3+ (229.5/232.6 eV), Mo 5+ (232.0/235.0), and Mo 6+ (233.5/235.8 eV) [ 43 , 44 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…So far, different electrochemical conditioning methods (e.g., CP, CA, and CV) have been employed without clear distinction for various OER electrocatalysts and random electrochemical activation results (e.g., degree of in situ oxidation and Fe incorporation) have been reported. 10,[15][16][17][18][19][20][21][22][23][24] Kim et al conducted CV electrochemical conditioning for Co3C and observed its complete in situ oxidation to amorphous CoOx. 22 Kawashima et al conducted CV electrochemical conditioning for Ni3N/Ni foam in Fepurified and Fe-unpurified KOH electrolyte and observed its partial in situ oxidation and Fe incorporation into Ni3N/Ni.…”
Section: Introductionmentioning
confidence: 99%
“…22 Kawashima et al conducted CV electrochemical conditioning for Ni3N/Ni foam in Fepurified and Fe-unpurified KOH electrolyte and observed its partial in situ oxidation and Fe incorporation into Ni3N/Ni. 23 In comparison, Trotochaud et al carried out CP electrochemical conditioning for NiO and observed its complete in situ oxidation to NiOxHy in alkaline media (1 M KOH). 10 Selvam et al conducted CA electrochemical conditioning for Ni(OH)2/Co9S8 in 1 M KOH electrolyte containing 1 ppm of Fe ions and observed its complete in situ oxidation and Fe incorporation to form Fe-doped NiOOH/CoOOH.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 1 ppm of Fe is a significant addition that substantially improves the OER activity. Moreover, the potentials of the Ni 4+/3+ redox peaks were slightly shifted after immersion in 1 ppm Fe aq electrolyte ( Figure 2 b) [ 18 , 29 , 30 ], evidencing that Fe incorporates/adsorbs on the surface, increasing the capacity of the cathodic peak, which is related to the formation of a thicker or more redox active Ni-Fe (oxy)hydroxide layer [ 8 , 30 ]. The LCFN43 sample demonstrates an activity improvement factor (ratio of current values in the 1 ppm Fe aq electrolyte and in the pristine electrolyte) equal to 3.9.…”
mentioning
confidence: 99%